The Therapeutic Collaboration in Dropout Cases of Narrative Therapy: An Exploratory Study - Pinto, Dulce; Sousa, Inês; Pinheiro, Ana; Freitas, Ana Cláudia; Ribeiro, Eugénia (Revista de Psicoterapia, 2018)
With this study, we aimed to describe the interaction within the therapeutic dyads involved in dropout cases of narrative therapy, once the quality of interaction in therapy appears to constitute a critical factor in clients’ decisions regarding its discontinuation. Seven dropout cases of narrative therapy, which were conducted by the same therapist, were analyzed using the Therapeutic Collaboration Coding System. The coding procedure required two trained and independent judges along with an auditing process. Overall, the findings demonstrated that independent of the clients’ responses, the therapist tended to increase the challenging interventions and decrease the supporting interventions over time. In turn, the clients oscillated between having experiences of safety and experiences of intolerable risk. The results will be discussed in terms of their theoretical and empirical relevance in relation to clinical implications.